Análisis de brechas del personal de la empresa METROCAR S.A. agencias Portoviejo y Manta período 2022-2023 - Zambrano Hidrovo, Génesis Jamileth (2023)
There are companies, organizations and cooperatives that present some shortcomings in their personnel management as a gap is found between the position and the worker's profile, causing weaknesses in work efficiency that could have a severe impact on business development, productivity and profitability. Due to this situation, the objective of this research is to analyze the gaps in the personnel of the company Metrocar S.A., period 2022-2023 to determine a training plan that contributes to the management of its human resources. The methodology used was guided by inductive, deductive, quantitative and qualitative methods, it is a bibliographic and field research, the survey, interview and gap analysis were used as information collection techniques, the instruments of which were questionnaires and matrices. Among the findings, it stands out that a large part of the staff is trained and university trained, the highest percentage of workers is destined for the sale of vehicles, the staff likes to receive training courses, there are deficiencies in the training policies for the staff, which implies a lack of specific guidelines to update the training of workers' knowledge. It is concluded that there is a lack of knowledge about gap analysis and they lack a training plan articulated with the institutional strategic plan. Of the positions analyzed there are workers with existing gaps. The training plan was carried out according to the needs identified with technical, economic and environmental feasibility.